Superparamagnetic Bifunctional Bisphosphonates Nanoparticles: A Potential MRI Contrast Agent for Osteoporosis Therapy and Diagnostic - Y. Lalatonne; M. Monteil; H. Jouni; J. M. Serfaty; O. Sainte-Catherine; N. Lièvre; S. Kusmia; P. Weinmann; M. Lecouvey; L. Motte (Journal of Osteoporosis)
A bone targeting nanosystem is reported here which combined magnetic contrast agent for Magnetic Resonance Imaging (MRI) and a therapeutic agent (bisphosphonates) into one drug delivery system. This new targeting nanoplatform consists of superparamagnetic γFe2O3 nanoparticles conjugated to 1,5-dihydroxy-1,5,5-tris-phosphono-pentyl-phosphonic acid (di-HMBPs) molecules with a bisphosphonate function at the outer of the nanoparticle surface for bone targeting. The as-synthesized nanoparticles were evaluated as a specific MRI contrast agent by adsorption study onto hydroxyapatite and MRI measurment. The strong adsorption of the bisphosphonates nanoparticles to hydroxyapatite and their use as MRI T2∗ contrast agent were demonstrated. Cellular tests performed on human osteosarcoma cells (MG63) show that γFe2O3@di-HMBP hybrid nanomaterial has no citoxity effect in cell viability and may act as a diagnostic and therapeutic system.